2003
DOI: 10.1002/art.11130
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell uptake of human apoptotic and necrotic neutrophils inhibits CD40, CD80, and CD86 expression and reduces allogeneic T cell responses: Relevance to systemic vasculitis

Abstract: Objective. There is a breakdown of tolerance to neutrophil components during systemic vasculitis, which is marked by autoantibodies and T cells with specificity for proteinase 3 or myeloperoxidase, expressed on the surface of apoptotic neutrophils. This study was undertaken to investigate the effects of human apoptotic and necrotic neutrophils on human dendritic cell (DC) phenotype and ability to stimulate allogeneic T cell proliferation.Methods. DCs were generated from human peripheral blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 53 publications
(56 reference statements)
5
53
3
1
Order By: Relevance
“…The inability of apoptotic PMNs to activate DCs shown here is consistent with the reported capacity of such PMNs to elicit down-regulation of costimulatory molecules on DCs [36]. We found that CD40-increased expression appears to be mediated by soluble factors released by the PMNs, whereas HLA-DR and CD86 increase on DCs requires direct contact with PMNs.…”
Section: Discussionsupporting
confidence: 90%
“…The inability of apoptotic PMNs to activate DCs shown here is consistent with the reported capacity of such PMNs to elicit down-regulation of costimulatory molecules on DCs [36]. We found that CD40-increased expression appears to be mediated by soluble factors released by the PMNs, whereas HLA-DR and CD86 increase on DCs requires direct contact with PMNs.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this, PMNapo reduce the antigen-presenting capabilities of DC in healthy PPD + controls as well as in TB patients, which is a clear indication of the presence of a memory Mtb-specific immune response. Nevertheless, our results showing that PMNapo reduce but not abrogate the DC-specific response against Mtb are in contrast with those observed with MLR assay [22], which is critically dependent on the surface expression of HLA-DR and CD86 molecules on DC, thus, minimal changes in these parameters could be dramatically reflected in the results. Interestingly, while lower numbers of PPD + -DC induce specific lymphocyte proliferation, higher numbers of DC were needed to achieve the maximum response in TB patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Besides, as we herein demonstrate, supernatants from PMN Mtb do induce maturation in DC, which could be ascribed to TNF-a and IL-1b secreted during the process of Mtb-induced PMN apoptosis, as we have previously observed [12], the cytokines known to trigger DC maturation [22,24]. Hence, PMN…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The innate immunity may be terminated after the phagocytosis of apoptotic neutrophils but apoptotic neutrophils might also contribute the development of adaptive immunity because bacteria and bacterial products in the inflammatory loci may be cross-presented by macrophages or DCs phagocytosing apoptotic neutrophils (van Gisbergen et al, 2005). It was reported that the uptake of apoptotic neutrophils by DCs leads to the enhanced expression of CD83 and MHC-II on the DCs but a reduced capacity of DCs to stimulate mixed leukocyte reaction (Clayton et al, 2003). Positive staining of CD83 by an immunohistochemical assay in the inflammatory sites might involve both aged and apoptotic neutrophils (Iking-Konert et al, 2002).…”
Section: Discussionmentioning
confidence: 99%